Factor VII deficiency and developmental abnormalities in a patient with partial monosomy of 13q and trisomy of 16p: case report and review of the literature - Meck Jeanne M; Brooks Brian P; Haddad Bassem R; Bendavid Claude; Blain Delphine; Toretsky Jeffrey A (BMC, 2006)
Abstract Background Unbalanced chromosomal translocations may present with a variety of clinical and laboratory findings and provide insight into the functions of genes on the involved chromosomal segments. Case Presentation A 9 year-old boy presented to our clinic with Factor VII deficiency, microcephaly, a seizure disorder, multiple midline abnormalities (agenesis of the corpus callosum, imperforate anus, bilateral optic nerve hypoplasia), developmental delay, hypopigmented macules, short 5th fingers, and sleep apnea due to enlarged tonsils. Cytogenetic and fluorescence in situ hybridization analyses revealed an unbalanced translocation involving the segment distal to 16p13 replacing the segment distal to 13q33 [46, XY, der(13)t(13;16)(q33;p13.3)]. Specific BAC-probes were used to confirm the extent of the 13q deletion. Conclusion This unique unbalanced chromosomal translocation may provide insights into genes important in midline development and underscores the previously-reported phenotype of Factor VII deficiency in 13q deletions.